Person Centred Primary Care Diabetes - Sanjay Kalra; Madhur Verma; Nitin Kapoor (Journal of the Pakistan Medical Association, 2026)
This opinion piece highlights the importance of person centred philosophy in primary care. The authors define, describe and detail the concepts of person centred and responsible person centred care. They call for equal emphasis on evidence-based treatment, empathic delivery, experiential learning, ethical guidelines and environmental constraints. Keywords: Diabetes, person centred care, psychological aspects, primary care, responsible person centred care..